G217 Transforming children's nursing within a healthcare organisation through an innovative leadership approach. (27th April 2015) - Manning, JC; Coad, J
Abstract : Introduction: Nationally, high quality, translational research that has a tangible impact on lives and outcomes is demanded by service users, commissioners and research funders (NIHR, 2013). However, without strong leadership firmly embedded within health organisations the impact on children's nursing remains limited in reaching its potential. Aim: This presentation will critically review the experiences of employing an innovative leadership approach to progress children's nursing research and evidence-based practice (EBP) culture, capacity and capability within a children's hospital, situated within a large NHS Trust. Methods: Despite demonstrable commitment from the senior nursing management, local implementation of the nursing research vision remained under-developed. Consequently, a local strategy that engaged key stakeholders and PPI was devised during 2013/4 to operationalise the vision within the children's hospital. An innovative approach was employed to fulfil this multifaceted and diverse remit. Results: Outputs to date included identifying research areas that aligned to local and national service priorities; the appointment of a clinical-academic children's nurse; the implementation of a training programme in knowledge translation and scholarly activities; and a funded partnership between a senior children's nursing research leader/professor and the healthcare organisation. Opportunities have been sought with potential for national multi-centre studies with other specialist children's health settings. Post graduate students have been identified and supported. Conclusion: The strategy employed contributes to transforming the children's nursing research and EBP culture within a healthcare organisation in the UK through an innovative leadership approach. This visionary strategy will be shared with delegates with the rationale for appointments and support, and there impact on organisational culture, outlined. Challenges and successes will be discussed including early exemplars and high level impact results. The results and presentation will be useful for all delegates in supporting and developing the culture of nursing research within healthcare organisations.